(untitled) (Analysis in Theory and Applications, 2016)
Suppose b=(b_1,…,b_m)(BMO)^m, I_α,m^Π b is the iterated commutator of b and the m-linear multilinear fractional integral operator I_α,m. The purpose of this paper is to discuss the boundedness properties of I_α,m and I_α,m^Π b on generalized Herz spaces with general Muckenhoupt weights.